COSTUME AND FEMINISM: CHARACTER IN FILM KARTINI - Sintowoko, Dyah Ayu Wiwid; Sari, Siwi Anjar (Capture : Jurnal Seni Media Rekam, 2022)
Film Kartini, particularly the mise-en-scene aspect, appears to represent an era in the nineteenth century. The study focuses on Kartini's costumes. The research problem is how characters are constructed in the Film Kartini through costumes. The qualitative research method was employed for this study, and data collection was conducted using purposive sampling, with five scenes from Film Kartini serving as the primary data. The findings indicate that the costume’s four components, namely the top cloth, the body cloth, the leg cloth, and the accessories, are closely related to the character’s physiological, sociological, and psychological dimensions. The physical appearance of Kartini's costumes in its four components accurately reflects the physiological dimension. Meanwhile, Kartini appears to come from a noble family on the social dimension. Finally, on the psychological dimension, Kartini expresses her optimism for feminism through her costumes and movements but is confronted by the clash of Javanese traditions.